Libras: o tempo e o espaço enquanto adjuntos adverbiais - Silva, Andre Dos Santos [UNIFESP] (2020)
This master thesis seeks to investigate the standard position of the so-called adverbial adjuncts of time, frequency, and place in the syntagmatic structure of the sentence in libras. Given the uniqueness and autonomy of the linguistic system, it is understood that libras must present significant patterns for temporal and locative relations in discourse through conventional signals in its system. Congenital deaf people who recounted a story shown to them on video, as well as recounting episodes of their lives, were analyzed, according to a questionnaire previously prepared to stimulate the appearance of the desired phrases to the research. As a partial result, there was a major appearance of time adverbial adjuncts at the beginning of the sentence, but appearances of time and frequency adverbial adjuncts at the end of the sentence, suggesting that commonly the adverbial frequency adjuncts succeed the canonical structure, and that there are earlier time adverbial adjuncts, later time adverbial adjuncts, relating to the canonical structure of sentence. Regarding the decoding of the semantics of place, there is considerable variation in its occurrence in a sentence and may appear as an adverbial adjunct of place, indirect object and also representations that will be discussed in this work to raise a reflection on the existence of a system representative of libras and their relationship to the conventional signal system.